The use of CAMS and DBT to effectively treat patients who are suicidal - Jobes, David A.; Rizvi, Shireen L. (Frontiers in Psychiatry, 2024)
Around the world, suicide ideation, attempts, and deaths pose a major public and mental health challenge for patients (and their loved ones). There is thus a clear need for effective clinical treatments that reliably reduce suicidal thoughts and behaviors. In this article we review the Collaborative Assessment and Management of Suicidality (CAMS) and Dialectic Behavior Therapy (DBT) which are two clinical treatments that rise to the highest levels of empirical rigor. Both CAMS and DBT are now supported by randomized controlled trials (RCTs), with independent replications, and meta-analyses. There are also supportive data related to training clinical providers to use CAMS and DBT with adherence. RCTs that investigate the use of both interventions within clinical trial research designs and the increasing use of these complementary approaches within routine clinical practice are discussed. Future directions for research and clinical use of CAMS and DBT are explored as means to effectively treat suicidal risk.